Double button battery ingestion - The "macaroon" sign - Emma Littlehales; Eric Levi; Nikki Mills; Russell Metcalfe; James Hamill (Elsevier, 2018)
Button (Disc) battery impaction in the esophagus is a time critical presentation with significant associated morbidity and mortality. We present the case of a 15-month old boy with an unwitnessed foreign body ingestion, and who was subsequently found to have two ingested lithium button batteries, which were lodged at the upper esophagus, distal to cricopharyngeus. We discuss the "macaroon sign" of two button batteries lying parallel to one another, with both positive poles facing each other, as this may be an unusual barrier to urgent identification of the impacted foreign body as batteries.0.25% acetic acid was used as a neutralising agent at the time of button battery removal (8 h after ingestion), based on published evidence that this effectively decreases tissue pH and mitigates the severity of the injury in animal models, whilst not increasing ambient tissue temperature as once thought [4]. Our patient had a significantly better clinical outcome than predicted from the severity of the burn at time of button battery removal, suggesting acetic acid used topically is a safe adjunct treatment of impacted ingested button batteries and may reduce the likelihood of serious long term sequelae. Keywords: Button battery, Caustic ingestion, Esophageal injury, Foreign body ingestion, Electrical injury, Acetic acid